RANCANG BANGUN SISTEM INFORMASI PENJUALAN POT PADA CV NUANSA HIJAU BERBASIS WEB - Savira Rahmawati (2020)
The internet can provide ease in the aspects of business activities. One of them is the utilization of e-commerce used to increase sales. CV Nuansa Hijau is a family business that is engaged in the industrial manufacturing of terrazzo pots and plants. At present, CV Nuansa Hijau does not have a web-based sales information system. The recording of order data is still using paper and is not computerized. In addition, customers who want to place an order through social media must wait for a reply from the marketing staff. That causes problems in managing order data and sales transaction data which requires a long time. The purpose of this research is to produce terrazzo pot web-based e-commerce to manage order data and incoming sales transactions. In addition, the system makes it easy for customers to know product information. The terrazzo pot web-based e-commerce is designed using prototyping methods. The system is built using MySQL databases, Bootstrap framework, and PHP, CSS, and Javascript programming languages. This information system uses the pre-order system. The information system is expected to assist in managing the order data, sales transactions, and the delivery product becomes easier, making it easier to create sales reports.